Physiotherapy management of spasticity - Boyd, Roslyn; Ada, L. (2008)
© Cambridge University Press 2008 and Cambridge University Press, 2009.Spasticity is one of the impairments affecting function following brain damage. If spasticity is only one of several impairments following brain damage, physiotherapists need to clarify how spasticity affects the ability to move. Historically, spasticity was seen as the major determinant of activity limitations. The difficulty in assessing the contribution of different impairments to activity limitations makes it possible for other impairments to be mislabeled as spasticity. The operational definitions and relative importance of spasticity are confounded by the issue of how spasticity affects growth and maturation in children with spastic-type cerebral palsy. An important component of the clinical management of brain damage is careful assessment of the contribution of various impairments to activity limitations. There are many pharmacological and surgical options available in the management of spasticity, which may be focal or general, reversible or permanent in action.